Job Satisfaction and Work Performance among Women Employees in Malaysia's Health Department - Asaari, Muhammad Hasmi Abu Hassan; Desa, Nasina Mat; Jamaluddin, Nur Ashikin (International Business Information Management Association (IBIMA), 2019)
This paper focuses on the women employees in a health department. A total of 211 women employees were consulted using self-administered questionnaires that produced a good response rate of 62%. This paper intends to understand the relationship between job satisfaction and work performance among women employees in the health department. Moreover, this effort also measures the impact of job satisfaction on work performance of those women employees. Analyses were made using correlation, regression, and demographic comparisons. Recommendations are suggested to top management and women employees that they must always strive to ensure job satisfaction is at an optimal level so that the direction of the organization can be achieved.